Adsorption Optimization for the Removal of Cadmium in Water by Aluminum (Hydr)oxide on Cation Exchange Resin - Nguyen, Trung Thanh; Phan Thi, Thuy My Loan; Nguyen Thi, Thuy; Le, Tri Thich; Nguyen Thi, Cam Tien; Nguyen*, Nhat Huy (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2022)
In this study, we prepared aluminum oxide/hydroxide on a cation exchange resin and applied it for removing Cadmium (Cd) in water. The characteristics of the synthesized materials were determined by X-ray diffraction, scanning electron microscopy, energy-dispersive X-ray spectroscopy, and Fourier transform infrared spectroscopy. The Cd removal tests were conducted in both batch and continuous adsorption experiments. The maximum treatment efficiency and adsorption capacity were determined to be 99.97% and 10 mg/g material, respectively, under the optimum conditions of 10 mgCd/L, 1 g/L of material, and pH 6.54 for 70 min at room temperature. The adsorption kinetics and isotherms followed pseudo-second-order kinetics and the Freundlich isotherm model, respectively. The adsorption of Cd on the material was mainly due to physical adsorption and was an exothermic process. This study gives an alternative method for heavy metal removal from water using a new, inexpensive, and available absorbent. Keywords: cadmium; adsorption; water treatment; optimization *Corresponding author: Tel.: (+84) 901964985 E-mail: nnhuy@hcmut.edu.vn